Possibility to locate the position of the H2O snowline in protoplanetary disks through spectroscopic observations. Issue Volume 13:Issue S332(2017) (4th September 2018) - Notsu, Shota; Nomura, Hideko; Walsh, Catherine; Honda, Mitsuhiko; Hirota, Tomoya; Akiyama, Eiji; Millar, T. J.
Abstract: Observationally measuring the location of the H2 O snowline is crucial for understanding the planetesimal and planet formation processes, and the origin of water on Earth. The velocity profiles of emission lines from protoplanetary disks are usually affected by Doppler shift due to Keplerian rotation and thermal broadening. Therefore, the velocity profiles are sensitive to the radial distribution of the line-emitting regions. In our work (Notsu et al. 2016, 2017), we found candidate water lines to locate the position of the H2 O snowline through future high-dispersion spectroscopic observations. First, we calculated the chemical composition of the disks around a T Tauri star and a Herbig Ae star using chemical kinetics. We confirmed that the abundance of H2 O gas is high not only in the hot midplane region inside the H2 O snowline but also in the hot surface layer and the photodesorption region of the outer disk. The position of the H2 O snowline in the Herbig Ae disk exists at a larger radius from the central star than that in the T Tauri disk. Second, we calculated the H2 O line profiles and identified that H2 O emission lines with small Einstein A coefficients (∼10 −6 − 10 −3 s −1 ) and relatively high upper state energies (∼ 1000K) are dominated by emission from the hot midplane region inside the H2 O snowline, and therefore their profiles potentially contain information which can be used to locate the position of the H2 O snowline. The wavelengths of the H2 O lines which are the best candidates to locate the position of the H2 O snowline range from mid-infrared to sub-millimeter, and the total line fluxes tend to increase with decreasing wavelengths. We investigated the possibility of future observations using the ALMA and mid-infrared high-dispersion spectrographs (e.g., SPICA/SMI-HRS). Since the fluxes of those identified lines from a Herbig Ae disk are stronger than those of a T Tauri disk, the possibility of a successful detection is expected to increase for a Herbig Ae disk.